2000
DOI: 10.1161/01.str.31.9.2055
|View full text |Cite
|
Sign up to set email alerts
|

Atherothrombotic Middle Cerebral Artery Territory Infarction

Abstract: Background and Purpose-MRI has superior capabilities for the detection of cerebral infarcts compared with CT. CT was used to locate infarcts in most previous studies of atherothrombotic middle cerebral artery (MCA) territory infarcts. Thus, there was a possibility of missing concomitant small infarcts. More accurate identification of topographic lesions in MCA territory with MRI may help to establish the pathogenesis of stroke. The present study determines topographic patterns, distribution of vascular lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Previous studies indicated that extracranial atherosclerosis is more common in the white population, whereas intracranial atherosclerosis is more frequent in the Black and Asian populations [26, 27]. Another report that intracranial large artery disease was observed in 71% of patients suffering from MCA infarcts in Korea supports the association between SCI and large artery disease as stroke mechanism suggested in our study [28]. In our study, the presence of aphasia in patients with SCI was found to be an excellent predictor of cortical ischemic lesions on DWI, but only a weak predictor of ipsilateral large artery disease, also in the case of MCA and ICA disease associated with a possible hemodynamic cause.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies indicated that extracranial atherosclerosis is more common in the white population, whereas intracranial atherosclerosis is more frequent in the Black and Asian populations [26, 27]. Another report that intracranial large artery disease was observed in 71% of patients suffering from MCA infarcts in Korea supports the association between SCI and large artery disease as stroke mechanism suggested in our study [28]. In our study, the presence of aphasia in patients with SCI was found to be an excellent predictor of cortical ischemic lesions on DWI, but only a weak predictor of ipsilateral large artery disease, also in the case of MCA and ICA disease associated with a possible hemodynamic cause.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with large subcortical infarcts reportedly show cardiogenic sources in 9–52% of cases [5,9,10,11,12,13,14] and stenosis of major arteries in 27–89.5% of cases [2, 5,9,10,11,12,13,14,15,16]. We stress that a cardiac source or stenosis of major arteries can cause a LSCI.…”
Section: Discussionmentioning
confidence: 92%
“…While a number of investigators have described MCA territory small cortical or pial territory infarcts with variable topographical patterns [22, 23], we noticed a number of cases in which a thin strip-like infarct was present within the interdivisional region of the MCA territory involving cortex and sometimes extending medially to the periventricular zone. Since the topography of these infarcts appeared to be quite stereotypic, there were a number of questions which we wished to explore.…”
Section: Introductionmentioning
confidence: 73%
“…In the study by Bang et al [23], in which MR/DWI lesion topography was linked to prognosis, their subgroup ‘other cortical infarcts’ most likely contained several cases although the illustrated cases were not typical of ours in that they were larger and wedge shaped in keeping with their presumed embolic aetiology. Min et al [22] correlated DWI infarct patterns with arterial lesions. Their ‘pial territory infarcts without insular infarct’ also may have contained some cases of strip infarction, although those illustrated were wedge-shaped, multiple, centrum ovale infarcts and sometimes near external borderzones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation